Scrutiny of Role of Indolamine Inhibition in Asthma Using Animal Model - M. Usman Ali khan, Zari Salahuddin, Maryam Saqib, M. Yasoob Ali Khan, Muhammad Asif Faheem, Tunseer Ahmed, (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Asthma is a debilitating chronic inflammatory disease of airway with frequent episodes of exacerbations. It confers great burden on health systems due to associated symptoms like cough, wheeze, chest tightness and shortness of breath. We have explored the effect of an important indoleamine inhibitor on important asthmatic parameters in this study. Aim: Exploration of an alternative pathway of indoleamine inhibition for the treatment of asthma in future. Methods: Forty Wester rats were divided into four groups (normal control, disease control, prednisolone treated, methyltryptophan treated) with ten animals each. Blood samples were collected for eosinophil count. PCR was performed for measuring the IL-5 expression of the lung tissue. Results:1MT significantly reduced the eosinophil levels and mRNA expression of IL-5 through indoleamine inhibition. Conclusion: The pathway of indoleamine inhibition has appeared significant for reducing the inflammation and allergic response in asthma. Further exploration of this pathway can open new dynamics for asthma treatment.